2022
DOI: 10.1039/d2ra02771b
|View full text |Cite
|
Sign up to set email alerts
|

RGD peptide-based lipids for targeted mRNA delivery and gene editing applications

Abstract: We developed RGD peptide based ionizable lipids, which can be formulated into LNPs for integrin-dependent targeted mRNA delivery and gene editing applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…In the evaluation of physicochemical properties, modification of GG-(EK) 4 -lipid and KK-(EK) 4 -lipid did not affect the particle size of mRNA-LNPs but increased the PDI ( Table 4 ). On the other hand, KK-(EK) 4 /mRNA-LNPs and GG-(EK) 4 /mRNA-LNPs showed encapsulation efficiencies comparable to those of unmodified mRNA-LNPs, and these encapsulation efficiencies were consistent with a previous report on the modification of peptide-modified lipids into mRNA-LNPs by self-assembly using a microfluidic device (Qin et al., 2022 ). In addition, in the evaluation of luciferase expression in A549 cells, KK-(EK) 4 /mRNA-LNPs showed higher expression than unmodified mRNA-LNPs and GG-(EK) 4 /mRNA-LNPs ( Figure 7 ).…”
Section: Discussionsupporting
confidence: 90%
“…In the evaluation of physicochemical properties, modification of GG-(EK) 4 -lipid and KK-(EK) 4 -lipid did not affect the particle size of mRNA-LNPs but increased the PDI ( Table 4 ). On the other hand, KK-(EK) 4 /mRNA-LNPs and GG-(EK) 4 /mRNA-LNPs showed encapsulation efficiencies comparable to those of unmodified mRNA-LNPs, and these encapsulation efficiencies were consistent with a previous report on the modification of peptide-modified lipids into mRNA-LNPs by self-assembly using a microfluidic device (Qin et al., 2022 ). In addition, in the evaluation of luciferase expression in A549 cells, KK-(EK) 4 /mRNA-LNPs showed higher expression than unmodified mRNA-LNPs and GG-(EK) 4 /mRNA-LNPs ( Figure 7 ).…”
Section: Discussionsupporting
confidence: 90%
“…The choice of delivery system can have a significant impact on the immunogenicity of RGD peptides, which may include liposomes, nanoparticles, and micelles, etc. It is needed to find the most suitable option for reducing immunogenicity while maintaining therapeutic efficacy 96–99 . Considering the diversity of major histocompatibility complex (MHC) alleles in different populations and races, designing personalized peptides based on an individual's MHC profile can help reduce the risk of immunogenicity 100 .…”
Section: Potential Immunogenicitymentioning
confidence: 99%
“…Strategies such as surface PEGylation or decoration with polyanions can typically enhance passive targeting, thereby improving the serum stability and extending the blood circulation of gene vectors. 76 On the other hand, the active targeting strategy for mRNA delivery is to use targeting molecules, such as antibody, mannose, Arg-Gly-Asp peptide (RGD), 77 Cys-Lys-Lys-Lys (CKKK), 78 which specifically bind to receptors that are overexpressed on the surface of target cells, enhancing the uptake of the mRNA delivery system by those cells. For example, Dong et al demonstrated RGD modified mRNA nanocomplexes exhibited prolonged blood circulation and yielded much higher mRNA expression in tumours via intravenous administration compared to non-cRGD nanoformulation.…”
Section: Challenges Faced By Polypeptide-mrna Nanocomplexesmentioning
confidence: 99%
“…Ionizable lipids, exemplified by their success in clinically approved lipid nanoparticle formulations, offer pH responsiveness, efficient endosomal escape, and a mimicry of natural cellular membranes. 3,77 On the other hand, polypeptides show advantages such as stimuli responsiveness, biodegradability, and a high degree of customization, making them valuable for applications that demand tailored and targeted nucleic acid delivery with a focus on adaptability to diverse biological environments. 10,34 Further investigation is needed to develop principles and strategies for the rational design of targeted mRNA polymeric carriers that can effectively target specific cells, tissues, and organs.…”
Section: Challenges Faced By Polypeptide-mrna Nanocomplexesmentioning
confidence: 99%